2012
DOI: 10.4172/2153-0602.1000114
|View full text |Cite
|
Sign up to set email alerts
|

Computational Analysis on the Role of GPM6A in Human Thyroid Cancer

Abstract: Thyroid cancer is one of the major cancers around the world. In this study the whole thyroid genome is systematically scanned in order to hit those molecular targets which are highly associated with thyroid cancer. To achieve this goal bioinformatics methodologies are combined. These include the high throughput microarray analysis combined with Serial analysis of gene expression. The results obtained revealed Glycoprotein M6A (GPM6A) as a novel associated gene marker. It belongs to the glycoprotein's family wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Furthermore, higher expression of GPM6A was observed in poorly differentiated colorectal cancers compared with highly differentiated cancers 23,24 . Papillary thyroid carcinomas express higher levels of GPM6A compared with normal thyroid tissue 25 . In primary B‐cell malignancies induced by the Graffi mouse leukemia virus in mice, GPM6A was also found to be overexpressed 22 .…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, higher expression of GPM6A was observed in poorly differentiated colorectal cancers compared with highly differentiated cancers 23,24 . Papillary thyroid carcinomas express higher levels of GPM6A compared with normal thyroid tissue 25 . In primary B‐cell malignancies induced by the Graffi mouse leukemia virus in mice, GPM6A was also found to be overexpressed 22 .…”
Section: Discussionmentioning
confidence: 97%
“…GPM6A has been described as differentially expressed in thyroid cancer, expressed at higher levels in papillary thyroid carcinoma as compared to normal thyroid tissue 16 . In primary B-cell malignancies induced by Graffi murine leukemia virus in mice, GPM6A was found to be over-expressed; ectopic expression of GPM6A in NIH 3T3 cells promoted cell proliferation and anchorage-independent cell growth in vitro 17 .…”
Section: Discussionmentioning
confidence: 99%
“…They found increased BAFF mRNA expression and concluded that the increase is not reflective of histological disease severity. A review article by Khalid et al [6] presents an overview of therapeutic use of retinoids, a group of natural and synthetic derivatives of vitamin A for LN. The review discusses the details of LN pathogenesis and severity in humans, and current and new agents for the treatment.…”
mentioning
confidence: 99%
“…Computational analysis of microarray data and serial analysis of gene expression enabled Khalid et al [6] to show that the protein GPM6A plays a major role in cell migration and is a major contributor in tumor formation. The results could lead to earlier diagnosis and better treatment for thyroid cancer patients.…”
mentioning
confidence: 99%